IMPLEMENTASI METODE PEMBELAJARAN DISCOVERY LEARNING PADA MATA PELAJARAN PPKN UNTUK MEMBENTUK CIVIC SKILL (STUDI DI KELAS VIII SMPN 1 JENANGAN, KABUPATEN PONOROGO) - Rahayu Riastuti, Eka; Surya Ningsih, Ruddat Ilaina; Puji Asmaroini, Ambiro; Cahyono, Hadi Cahyono (Universitas Muhammadiyah Ponorogo, 2018)
The subjects of Pancasila and Citizenship Education are implemented so that every citizen knows about the rights and obligations in running the life of nation and state. As a nation with a long history of struggle for independence, the love of the country, patriotism and nationalism must remain in every soul of Indonesian society. As the development of the era and technology, the values are increasingly decreasing, especially among school-age adolescents. The purpose of this study is to understand the implementation of learning discovery learning method in PPKn subjects in Junior High School 1 Jenangan Ponorogo Regency and to understand how to form civic skills through discovery learning method. This research method is descriptive qualitative first, to understand to comprehend implementation of learning discovery learning method in class VIII subject of PPKn at SMP Negeri 1 Jenangan Ponorogo Regency. Second, to understand how to form civic skill through discovery learning method in class VIII subject of PPKn in junior high school 1 jakarta Ponorogo regency. Implementation of learning discovery learning model in PPKn subjects in class VIII SMPN 1 by: 1) Stimulation (stimulation / stimulation), 2) Problem statement (statement / identification problem 3), Data collection (data collection). 4) Data Processing (data processing). 5) Verification (verification). 6) Generalization (drawing conclusions / generalizations).